A new creative Kurdish constitution in the Middle East. Issue 1 (2nd January 2017) - Radpey, Loqman; Rose, Gregory
Abstract : The uprising in Syria since 2011 has created opportunities for creative approaches to Kurdish self-rule. The decision of Bashar al-Assad's armed forces to withdraw from Kurdish cities in Northern Syria enabled Kurdish parties to take charge of local state institutions, declare self-rule, and to replace Syria's flags with their own. The Democratic Union Party (Syria) announced a new constitution on 21 July 2013 that it called a "social contract". On the basis of that constitution, Kurdish autonomous self-rule was formed comprising of three initial cantons. The principle of equality of all groups and the renunciation of the nation-state are revolutionary dimensions of the new constitution. In this paper, the new constitution's creative dimensions are described and analyzed using a descriptive-analytic approach. The study aims to describe the articles of the constitution to analyze how minority Yazidis, Armenians, Arabs, Christians, Chechens, and Kurds might promote this model for the rest of Syria as a form of "democratic federalism".